2008
DOI: 10.1038/oby.2008.379
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Adipose Tissue Extent: Relationship With Age, Body Fat Distribution, and Coronaropathy

Abstract: Epicardial fat is a relatively neglected component of the heart and could be an important risk factor of cardiac disease. The objective of our study was to assess the relationship between epicardial adipose tissue (EAT) extent, fat distribution, and coronaropathy in a group of adult victims of accidental or suspicious sudden death. In 56 cadavers, we performed 34 measurements of EAT from five computerized photographs of the heart (anterior and posterior faces, and three ventricle transversal slices) and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
99
2
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(115 citation statements)
references
References 26 publications
7
99
2
7
Order By: Relevance
“…We observed that aging was also associated with an increase in epicardial fat volume which may be due to a loss of lean body mass with an increase in fat mass and redistribution to the trunk and viscera which occurs with aging [20]. In contrast to the aortic PWV, the epicardial fat volume was significantly associated with BMI which is in concordance with previous studies [21,22]. We also observed a significant relationship between the epicardial fat volume and the aortic PWV.…”
supporting
confidence: 90%
“…We observed that aging was also associated with an increase in epicardial fat volume which may be due to a loss of lean body mass with an increase in fat mass and redistribution to the trunk and viscera which occurs with aging [20]. In contrast to the aortic PWV, the epicardial fat volume was significantly associated with BMI which is in concordance with previous studies [21,22]. We also observed a significant relationship between the epicardial fat volume and the aortic PWV.…”
supporting
confidence: 90%
“…In agreement with previous autopsy studies, or studies using Cardiac adiposity and heart function in obesity B Gaborit et al echography or computed tomography, EFV increases with age, BMI and waist circumference. 15,16,37,42 Surprisingly, EFV was not correlated with LV mass or EDV. Previous studies showed similar results.…”
Section: Discussionmentioning
confidence: 90%
“…25 EFV is an important fat depot and its abundance was clearly associated with the presence and severity of coronaropathy. 8,15,40 An inflammatory profile in patients with coronary disease was also enlightened, suggesting a pathophysiological link between EFV and the development or aggravation of coronaropathy. 5,8,9,41 This study provides a detailed characterization of the metabolic, inflammatory and cardiovascular parameters associated with EFV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive EAT has been reported to be associated with known cardiovascular risk factors 1,2) . Moreover, several investigators have shown that quantity of EAT can be a marker for the presence and severity of coronary artery disease (CAD) [3][4][5][6] . Computed tomography and Magnetic resonance imaging provide volumetric measurement of EAT, whereas echocardiography determines only the thickness of regional EAT.…”
Section: See Article Vol 22: 582-589mentioning
confidence: 99%